Evaluation of the impact of organizational learning on teacher training - Chavez Castillo, Elizabeth Raquel; Chavez Castillo, Mirtha Betsabé; Chavez Castillo, Rebeca Lizeth; Arce Otoya, Miguel Ernesto (Universidad Ciencia y Tecnología, 2024)
Organizational learning is a continuous, adaptive process through which an organization improves its ability to achieve its objectives and goals. In this work, the impact of organizational learning on the performance of teachers in public institutions has been evaluated. It was carried out with a quantitative approach, a descriptive-explanatory, correlational design and a sample made up of 120 basic education teachers. The results revealed that there is a positive correlation between both variables and therefore, institutions must focus on the acquisition of knowledge, skills, perspectives and practices that allow them to face and adapt to changes in their environment, as well as improve their performance. the long of the time. time.